PERENCANAAN SISTEM PEMBELAJARAN PAI BERBASIS PROYEK UNTUK PENINGKTAN KETERAMPILAN BERPIKIR KRITIS SISWA DI MTS MALNU PUSAT MENES KABUPATEN PANDEGLANG - Dewi Afini; Mumu Zainal Mutaqin; Sanusi; Siti Humaeroh; Nurul Huda (Adz-Zikr : Jurnal Pendidikan Agama Islam, 2026)
This study aims to explore in depth how project-based planning in Islamic Religious Education (PAI) learning systems can help enhance students’ critical thinking skills at Madrasah Tsanawiyah Malnu Pusat Menes. The background of this research arises from the issue of students’ low ability to think critically in understanding and applying religious values in their daily lives. This condition is caused by the conventional and teacher-centered nature of PAI learning, which limits students’ active participation in the learning process. To address this challenge, the study focuses on the importance of innovative and contextual learning planning so that students can develop reflective and critical thinking toward the values they study. This research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The collected data were analyzed through stages of data reduction, data presentation, and conclusion drawing. The results reveal that project-based PAI learning planning is developed by considering students’ needs and characteristics, setting learning objectives relevant to real-life contexts, and designing meaningful and applicable projects. The implementation of this planning has proven effective in fostering students’ critical thinking skills through collaborative activities, problem-solving, and reflection on Islamic values embedded in the projects. Thus, project-based PAI learning planning contributes positively to improving the quality of the learning process and developing students’ critical thinking skills within the madrasah environment.